The confusion continues: results from an American Association for the Surgery of Trauma survey on massive transfusion practices among United States trauma centers. Issue 10 (11th August 2016) - Etchill, Eric; Sperry, Jason; Zuckerbraun, Brian; Alarcon, Louis; Brown, Joshua; Schuster, Kevin; Kaplan, Lewis; Piper, Greta; Peitzman, Andrew; Neal, Matthew D.
Abstract : BACKGROUND: Massive transfusion practices have undergone several recent developments. We sought to examine institutional practices guiding hemostatic resuscitation in the setting of massive hemorrhage. STUDY DESIGN AND METHODS: A 37‐question online survey was sent to American Association for the Surgery of Trauma members. RESULTS: A total of 191 surgeons from 125 institutions completed the survey. Level I and II centers composed 70 and 18% of responding sites, respectively. A total of 123 institutions have a massive transfusion protocol (MTP); 54% report having an MTP for less than 5 years. The number of coolers and units of red blood cells, plasma, and platelets are highly variable. Tranexamic acid is part of the MTP at 64% of centers; 26% continue to use recombinant activated Factor VII. MTP activation occurs more than five times per month at 32% of centers. MTPs are utilized for nontrauma patients in 82% of institutions. Point‐of‐care prothrombin time, international normalized ratio, and partial thromboplastin time testing is utilized in 37% of institutions. Only 9% routinely utilize thromboelastography or rotational thromboelastometry (TEG/ROTEM) within their MTP. Just 7% use a validated scoring system to guide MTP activation. The incorporation of TEG/ROTEM into the MTP is associated with the use of a scoring system in regression analysis (p = 0.024). CONCLUSION: Most institutions regularly activate recently implemented MTPs for trauma and nontrauma indications; however, few use validated scoring systems for MTP activation. MTP content is highly variable. Few institutions use TEG, while most have incorporated tranexamic acid into their protocol. The lack of consistent practices underscores the need for outcome‐based studies to guide transfusion practices.